Survey Perparkiran Fakultas Teknik Universitas Negeri Makassar - Taufiq Natsir; Panennungi T.; Onesimus Sampebua (SOCIETIES: Journal of Social Sciences and Humanities, 2021)
Abstract. Makassar State University has 9 faculties spread over several locations and one of them is the Faculty of Engineering which is located in Parangtambung. This faculty is one of the faculties that continues to work and continues to develop itself to achieve its vision and mission as one of the superior faculties with entrepreneurial insight. In recent years, we have continuously improved, both system reform, procurement of various laboratory equipment, improvement of infrastructure to create conducive academic conditions and one of them is fixing the parking lot, where in the last two years parking has been chaotic and needs to be fixed, so it is done. research with the title of UNM Faculty of Engineering Parking Survey. This research is a survey research that aims to determine the parking conditions and to determine the size of the parking area according to the needs and behavior to park the vehicles of the 2020 Faculty of Engineering academic community. Keywords: Survey, Parking, Faculty of Engineering